Growth of transcendental solutions to higher-order linear differential equations with entire coefficients - Karima Hamani (Electronic Journal of Differential Equations, 2016)
In this article, we study the growth of transcendental solutions of certain higher order linear differential equations with entire coefficients. Under some conditions, we prove that every transcendental solution is of infinite order. We also give an estimate of its hyper-order. We improve previous results by Peng and Chen [14].